Manuscript found in Accra - Coelho, Paulo (Thorsons, 2013)
"The latest novel from #1 internationally best-selling author Paulo Coelho is a classic of inspiration and reflection, a meditation on life, love, and the significance of change. A novel of philosophical reflection set in Jerusalem during the time of the Crusades. Here a community of Christians, Arabs, and Jews who have long lived together harmoniously have been warned of an imminent attack and certain destruction. Contemplating their demise, the community assembles to seek the wise counsel of a Greek Copt, who imparts comforting and guiding wisdom on the enduring attributes of human character. The novel unfolds as a sequence of parables on love, faith, sex, friendship, beauty, bravery, loyalty, and success. "-- Provided by publisher